2009
DOI: 10.1021/ja9068112
|View full text |Cite
|
Sign up to set email alerts
|

Enamine Catalysis with Low Catalyst Loadings - High Efficiency via Kinetic Studies

Abstract: Kinetic studies on enamine catalysis provided insight into the rate determining step(s) of peptide catalyzed conjugate addition reactions between aldehydes and nitroolefins. They demonstrate that not enamine formation but both the reaction of the enamine with the electrophile and hydrolysis of the resulting imine are rate limiting. These results allowed for reducing the catalyst loading by a factor of 10 to as little as 0.1 mol %. This is the lowest catalyst loading that has been achieved so far in enamine cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
115
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(120 citation statements)
references
References 34 publications
4
115
0
1
Order By: Relevance
“…[28] Davis and co-workers adopted this strategy and synthesized a bifunctional catalyst by introducing amine and sulfonic acid groups on mesoporous silica, which dramatically increased the activity due to cooperativity between both groups. [25,26] Solin and collaborators, as well as Thiel and co-workers, obtained similar results, using different combinations of alkylamines and acidic groups in mesoporous silica supports. [23,27] However, the poor catalytic activity of monofunctional amine on silica, which remains commonly used for the aldol and similar types of condensation, [20,22,24,[29][30][31][32] is still not well understood.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…[28] Davis and co-workers adopted this strategy and synthesized a bifunctional catalyst by introducing amine and sulfonic acid groups on mesoporous silica, which dramatically increased the activity due to cooperativity between both groups. [25,26] Solin and collaborators, as well as Thiel and co-workers, obtained similar results, using different combinations of alkylamines and acidic groups in mesoporous silica supports. [23,27] However, the poor catalytic activity of monofunctional amine on silica, which remains commonly used for the aldol and similar types of condensation, [20,22,24,[29][30][31][32] is still not well understood.…”
Section: Introductionmentioning
confidence: 64%
“…The role of silanols in the reaction can be explained by the fact that carbonyl compounds adsorb on the surface of silica via hydrogen bonding. [26,[51][52][53][54][55][56] We confirmed this interaction by measuring NMR spectrum of 13 C-labeled acetone set in contact with non-functionalized MSN (Figure S6), which exhibited a downfield shift of the carbonyl carbon signal compared to that of neat acetone (~213 ppm versus 206 ppm). Our earlier solid-state NMR and theoretical studies demonstrated that surface silanols on silica also interact with the amine functionalities.…”
Section: Cooperative Effects Of the Supportmentioning
confidence: 78%
See 2 more Smart Citations
“…Nevertheless, a recent study revealed that in addition to the reaction of the enamine with the nitroalkene, the hydrolysis of the enamine is also rate limiting in some extent. [21] The absolute configuration (R) was determined by comparison of the optical rotation values for adducts 8d [22] and 8i [23] with that previously reported in the literature for the same product. We assume the same TS and therefore the same configurational assignment for the rest of products 8a-m.…”
mentioning
confidence: 99%